INTERPRETATION BLACK CAMPAIGN IN SHORT MESSAGE SERVICES AT ELECTION OF MAYOR MAKASSAR 2013 - Christiany Juditha (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2014)
Direct elections of regional heads is synonymous with the campaign to sell the product, the idea of social change, as well as leadership candidates. The goal is to obtain the support of the voters. It's just reality, many campaigns to attack political opponents in the form of black campaign through a variety of media, including SMS (Short Message Service). It also occurs in Makassar Mayor Election 2013. This interesting phenomenon to be studied in order to get an overview of discourse black campaign in the local elections. This study uses discourse analysis to refer to the concept Van Dijk. The study says that there are 12 SMS containing black campaign during the election campaign the Mayor of Makassar 1 -18 September 2013. The entire SMS is aimed at the 2 pair that is only mayoral candidate pair number 2 is SUKA (Supomo Guntur and Kadir Halid) and a couple mayor serial number 9 is NOAH (Irma Yasin Limpo and Busrah Abdullah). Prominent theme of this message is a resistance movement dynasty of Sahrul Yasin Limpo and Nurdin Halid and rejection of corruption. The entire message clearly illustrates the negative image of both the Makassar mayor candidates.Keywords: Interpretation, Black Campaign, SMS, Elections.